Production of smart polymer blend filament from waste PET obtained water bottles: investigation of thermal and shape memory behavior - Oner, Ecem Ozen; Kok, Mediha; Pekdemir, Mustafa Ersin; Aydogmus, Ercan; Saydam, Sinan; Aydogdu, Yildirim (Polymer Soc Korea, 2024)
Waste (polyethylene terephthalate) (PET) water bottles are among the most common plastic wastes in nature. These plastic wastes disappear within hundreds of years after they are released into nature. Therefore, it causes serious environmental pollution. Therefore, it is important to make these wastes reusable. This study aims to bring a new perspective to the reuse literature. It is aimed to produce smart polymer blend from waste PET, which is highly demanded and important in practical applications. Therefore, in this study, waste polymer PET was blended with smart polymer PLA into filament blends. The thermal properties of the blends were analysed by Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA), chemical bond structures were determined by Attenuated Total Reflectance-Fourier transform infrared spectroscopy (ATR-FTIR spectroscopy) and shape memory tests were performed to determine whether the blends exhibit smart material properties. As a result of this study, it was observed that the thermal stability of the blended filaments varied according to the polymer ratio and the blend was characterized as an immiscible polymer blend. It was also found that the polymer blends exhibit shape memory properties.
Keywords: Waste; Water bottle; Filament; Smart polymer; Blend